Vitamin B12 Deficiency Observed in Children With First Afebrile Seizures - Kirik, Serkan; Catak, Zekiye (Springernature, 2021)
Objective: Vitamin B12 deficiency can lead to many different types of neurological symptoms and seizure can be seen as the first symptom. In the present study, we aimed to evaluate patients with seizures who were found to have vitamin B12 deficiency and whose seizures resolved with vitamin B12 treatment. Methods: A total of 26 infants were included in this retrospective study. The patients were evaluated in terms of clinical findings, laboratory tests including homocysteine, electrophysiological studies, neuroimaging studies, and other neurological examination findings. Results: Of 26 patients, 14 (53.8%) were male. The mean age of the patients was 8 +/- 4.8 months. Sixteen patients had generalized tonic-clonic seizures, and two patients had epileptic spasm (West syndrome)-type seizures. Six patients had abnormal discharge on electroencephalography. Twelve patients had abnormal findings in brain magnetic resonance imaging studies. Homocysteine level was high in all patients at admission. Conclusion: The presence of seizures, including infantile spasm, is a very important and treatable manifestation of vitamin B12 deficiency. Considering the irreversible sequelae of increased homocysteine, vitamin B12 supplementation administered for an appropriate period and at an appropriate dose both prevents the use of unnecessary antiepileptic drugs and eliminates the need for unnecessary tests and examinations.
Keywords: vitamin b12; homocysteine; seizure; infantile